Innovative Materials and Processes for Removal of Biopersistent Pollutants - Petrella, Andrea; Race, Marco; Spasiano, Danilo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Hazardous artificial contaminants are molecules of inorganic and organic nature (pharmaceuticals, food sources, heavy metals, dyes, personal care products, detergents, flame retardants, cosmetics, and pesticides) with potential toxicological effects on human health and the environment (air, water, and soil) due to their ubiquity at trace levels. These products could be bio-persistent during conventional treatment processes; accordingly, the adoption of proper and innovative technologies is necessary for the removal of these hazardous, persistent chemicals before their release into the environment. The aim of this reprint, entitled "Innovative Materials and Processes for the Removal of Biopersistent Pollutants", was to collect studies devoted to the recent progress and new perspectives in the treatment and removal of hazardous artificial contaminants in the air, soil, and water supply.